2018
DOI: 10.1021/acs.jpcb.8b10077
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Structure Analysis of a Hemoglobin Core in Hemoglobin–Albumin Cluster

Abstract: A core–shell ensemble of bovine hemoglobin (Hb) and human serum albumin (HSA) is an artificial O2 carrier as a red blood cell substitute. This protein particle is created by covalent wrapping of a carbonyl Hb with HSAs: HbR–HSA 3 cluster, where HbR signifies the use of carbonyl Hb (relaxed (R) state conformation) as a starting material. The HbR–HSA 3 cluster exhibits high O2 affinity and low cooperativity. Analysis of the quaternary structure of the central HbR in the cluster revealed that its high O2 affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…As reported previously, the Hb‐HSA 3 cluster displayed low P 50 and n values ( P 50 : 8 torr, n= 1.4), relative to those of native Hb ( P 50 =12 torr, n= 2.4; Table ) . The reductions are attributed to chemical modifications of Cys‐β93 and surface Lys groups of R‐state Hb (raw material) by SMP . In particular, the covalent binding of bulky SMP to the Cys‐β93 residue interrupts the formation of the His‐β146 ⋅⋅⋅ Asp‐β94 salt bridge and destabilizes the T state (Figure B).…”
Section: Figurementioning
confidence: 55%
See 4 more Smart Citations
“…As reported previously, the Hb‐HSA 3 cluster displayed low P 50 and n values ( P 50 : 8 torr, n= 1.4), relative to those of native Hb ( P 50 =12 torr, n= 2.4; Table ) . The reductions are attributed to chemical modifications of Cys‐β93 and surface Lys groups of R‐state Hb (raw material) by SMP . In particular, the covalent binding of bulky SMP to the Cys‐β93 residue interrupts the formation of the His‐β146 ⋅⋅⋅ Asp‐β94 salt bridge and destabilizes the T state (Figure B).…”
Section: Figurementioning
confidence: 55%
“…The groups of Rosa and Ho reported that capping of Cys‐β93 of Hb with N ‐ethylmaleimide or other sulfhydryl reagents also increased the O 2 affinity and weakened the IHP effect. We previously reported the synthesis of a core–shell‐structured protein cluster comprising of Hb and human serum albumin (HSA), the Hb‐HSA 3 cluster, as a promising HBOC . The Hb‐HSA 3 cluster has shown initial preclinical safety and long circulation persistence in the bloodstream .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations